1996
DOI: 10.1136/bmj.312.7036.935
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of chylomicron remnants in normolipidaemic patients with coronary artery disease: case control study over three years

Abstract: Normolipidaemic patients with coronary artery disease had significantly higher concentrations of chylomicron remnants in plasma than normolipidaemic subjects with normal coronary vessels. This may explain the mechanism underlying the susceptibility to atherosclerosis of coronary artery disease patients with normal fasting lipid values. As diet and drugs can ameliorate the accumulation of postprandial lipoproteins in plasma, the concentration of chylomicron remnants should be measured in patients at high risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
1
12

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(135 citation statements)
references
References 40 publications
4
118
1
12
Order By: Relevance
“…Peak and late postprandial triglyceride concentrations have been associated with coronary atherosclerosis [7,26,27] and early carotid atherosclerosis [8,28]. Furthermore, postprandial retinyl palmitate concentrations, reflecting postprandial concentrations of chylomicrons and chylomicron remnants, are associated with CHD in case-control studies [29,30] and postprandial plasma concentrations of small chylomicron remnants are related to progression of coronary lesions as determined by sequential coronary angiographies [31].…”
Section: Discussionmentioning
confidence: 99%
“…Peak and late postprandial triglyceride concentrations have been associated with coronary atherosclerosis [7,26,27] and early carotid atherosclerosis [8,28]. Furthermore, postprandial retinyl palmitate concentrations, reflecting postprandial concentrations of chylomicrons and chylomicron remnants, are associated with CHD in case-control studies [29,30] and postprandial plasma concentrations of small chylomicron remnants are related to progression of coronary lesions as determined by sequential coronary angiographies [31].…”
Section: Discussionmentioning
confidence: 99%
“…42 The clinical relevance of this may be evident from recent case-control studies; postprandial plasma concentrations of TAG are strongly predictive of the presence or absence of CVD. 6,43,44 Thus, there is increasing research interest in the study of metabolic events during the postprandial period and of interventions, including exercise, which modify these.…”
Section: Exercise and Postprandial Lipid And Lipoprotein Metabolismmentioning
confidence: 99%
“…1 Several studies have described abnormalities in postprandial metabolism in patients with coronary artery disease, 2 ± 4 and shown that postprandial triglycerides (TG) are independent predictors of coronary artery disease in multivariate analysis, 5 even after adjustment for fasting TG or HDL-cholesterol in normolipidemic men. 6 Obesity is associated with abnormal fasting lipid parameters such as increased fasting triglyceride and decreased HDL-cholesterol, 7 which could explain, at least in part, the greater development of cardiovascular disease in obese people. Nevertheless, obesity appears to be an independent risk factor for coronary artery disease, even in subjects with normal fasting plasma lipids and normal glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%